No reserve - Francis, Felix (Francis, Felix. Dick Francis novel ;, 2023)
"Theo Jennings, an auctioneer in Newmarket, England, has been climbing the ladder at the bloodstock sales company for the past three years. He's planning on making his first ever multi-million sale with a yearling colt. When he finds the colt dead a few days after the auction, Theo is suspicious that there was foul play involved. As Theo begins to investigate the death, he finds that answers aren't coming readily from those who he questions. When a person's body is discovered in the same stable a few days later, all fingers point to him. As his world turns upside down with the accusations, Theo decides to further his investigation. The only way to clear Theo's name is to find the real murderer, but it isn't just the police who have their eye on him--the killer has a target on his back"--